Swimming propulsion and muscle force moments - Hildebrand, F.; Schüler, A. (Mathematical and Computer Modelling of Dynamical Systems, 2010)
Based on 3D video analysis of swimming movements hypotheses on the mechanisms of propulsion are deduced. Body point coordinates and their first and second derivatives are computed. The limb environment where water particle displacement occurs is estimated. We apply the Navier-Stokes equation to compute the total force for those particles. The shoulder torque is calculated by summation over environments of hand, forearm and upper arm of infinitesimal torques of displaced water particles. Similarly, hip torques are computed by summation over environments of foot, shank and thigh. Our aim is to determine individual shoulder and hip torques over one movement cycle. These muscle force moments are related to the velocity of the mass centre as a measure for propulsion. Simultaneously they serve as controlling data for dry land strength training. Recommendations for best propulsion techniques are derived.